ANALISIS KEMAMPUAN PENALARAN MATEMATIS DALAM MENYELESAIKAN SOAL KUBUS DAN BALOK DITINJAU DARI GAYA KOGNITIF FIELD INDEPENDENT DAN FIELD DEPENDENT - Mustofah Mustofah; Ali Shodikin; Abdur Rohim (INSPIRAMATIKA, 2020)
This study aims to determine the ability of mathematical reasoning in solving problems in cube and beam material in terms of independent and dependent field cognitive styles. This type of research is a qualitative descriptive study. The data collection method is carried out by the test and questionnaire method. The study was conducted by giving 2 written test items about solving cube and beam problems as well as a questionnaire of independent and field dependent cognitive style tests at the beginning and end of the study. Data analysis techniques used are data reduction, data presentation and conclusion / verification. The results of the study show: (1) the test results of students' mathematical reasoning questions with independent field cognitive style on cube and beam material are able to pass 4 indicators better than students with field dependent cognitive style; (2) the test results of students' mathematical reasoning questions with the field dependent cognitive style on the cube and beam material are only able to go through 2 lower indicators than students with independent field cognitive style.